Examining the Role of Pre-Instruction Academic Performance Within A Text-based Approach to Improving Student Content Knowledge and Understanding. (January 2019) - Wanzek, Jeanne; Roberts, Greg; Vaughn, Sharon; Swanson, Elizabeth; Sargent, Katherine
Students with disabilities are often included in general education social studies classes, but these classes can differ in the achievement level of the overall class, including wide variation in content-related background knowledge, reading achievement, or both. The purpose of this study was to examine how background knowledge and reading achievement moderate the effects of a previously validated intervention, Promoting Adolescents' Comprehension of Text (PACT). We examined data from a prior randomized control trial of 1, 487 eighth-grade students in 85 classes that were randomly assigned at the class level to receive either PACT instructional practices or typical instructional practices using the same social studies content. Results of the current study reveal no moderating effect at the class level of either initial background knowledge or reading achievement on student content knowledge acquisition or content reading comprehension outcomes. Classes with varying levels of background knowledge and reading achievement performed similarly in PACT instruction, with benefits of the PACT instruction found on content knowledge acquisition.